Assessment of Knowledge, Attitudes, and Behaviors of Turkish Women on Breast and Cervical Cancer in Karabük Province, Turkey - Sevinc, Nergiz; Oral, Belgin; Korkut, Burcu (Kesmas, 2020)
Breast and cervical cancer incidence and mortality among women have been increasing worldwide. This cross-sectional study aimed to evaluate women's knowledge, attitudes, and behaviors regarding breast and cervical cancers. The sample was composed of 507 women aged 18 years and older who were admitted to a primary health care center in Karabük, Turkey, from October to December 2019. The data was obtained using a questionnaire consisting of 34 questions regarding participants’ socio demographic characteristics, knowledge, attitudes, and behaviors toward breast and cervical cancers. The mean age of the participants was 41.3±12.0 years and 68.4% of them were married. Slightly more than seven in ten participants knew that the most common cancer in women was breast cancer. Almost six in ten knew that breast self-examination was the first method in the early diagnosis of breast cancer. Breast self examination practice was found to be significant among university graduates. Periodic mammography and pap smear screenings among participants were 21.9% and 23.3%, respectively. Only 3.4% of participants had received the HPV vaccine and there was no significant difference between socio-demographic characteris tics and HPV vaccination status (p-value > 0.05). Participants had moderate knowledge about breast and cervical cancer. Access to cancer screening programs should be facilitated and increased, considering these cancers' public health importance.